Canine Transmissible Venereal Tumor: Anatomical Locations, Chemotherapy Response, and Epidemiological Aspects at a Veterinary Teaching Hospital in Brazil (2012–2022) - Pedro Antônio Bronhara Pimentel; Lorena Diniz Macedo Silva Maia; Isadora Maria Sátiro de Oliveira; Camila Stefanie Fonseca de Oliveira; Antonio Giuliano; Angel Almendros; Rodrigo dos Santos Horta (Animals)
Canine transmissible venereal tumor (CTVT) is a contagious neoplasm with low metastatic potential, primarily affecting free-roaming and stray dogs. Despite its global presence, epidemiological data from some regions remain limited. This study employed a retrospective observational design and analyzed 131 CTVT cases diagnosed via cytology or histopathology at a veterinary teaching hospital in Belo Horizonte, Brazil, aiming to describe the anatomical distribution, treatment outcomes, and epidemiological patterns. Most affected dogs were mixed-breed (70.2%) and female (61.1%), with a median age of 4.5 years. Genital involvement was most common (87.0%), followed by cutaneous (10.7%), nasal (6.1%), and oral (4.6%) tumors. Concurrent tumor locations included genital-cutaneous (5.3%) and oronasal (3.1%). Females had more genital cases, while males were more likely to present cutaneous and nasal CTVT, with 5.2 times greater odds for nasal tumors (OR = 5.2; 95% CI = 1.2–25.9). Purebred dogs also had increased odds of nasal involvement (OR = 8.2; 95% CI = 1.9–40.7). Vincristine chemotherapy was effective, and the number of sessions required for a complete response was not associated with clinical presentation, breed or size. These findings highlight the varied presentations of CTVT and reinforce the need for clinical awareness of non-genital forms.